Evaluasi Tingkat Kebisingan Di Bandar Udara Yogyakarta International Airport - Dimas Indra Kusuma; Triatmi Sri Widyaningsih*; Maria R Srah Darmanijati (Jurnal Teknologi, 2022)
Yogyakarta International Airport is a new airport but for aircraft mobility operational activities it is very crowded and crowded. Therefore, noise is often heard from the airport due to the mobilization of aircraft taking off and landing. The noise can interfere with health if it passes the predetermined quality standards. The purpose of the study was to determine the level of noise concentration, to determine the effect of wind speed and temperature on the noise level in the apron area of Yogyakarta International Airport. To find out the noise level and other parameters that can affect noise, the writer uses the independent and dependent variable method. The independent variables are the type of aircraft, the value of temperature/temperature and wind speed. The dependent variable in this study is the noise value generated from take off and landing activities in the airside area of the airport with units of db using a sound level meter. From the results of descriptive statistical analysis, the maximum noise value is 97.7 Db and the average noise value during landing and take off is 93,512 dB and 92.80 Db. This value is still below the quality standard based on the IATA (International Air Transportation Association) document and the Decree of the Minister of Transportation No. 48 of 2002 concerning the operation of public airports. And the parameter value of temperature/temperature is 0.231 and the value of wind speed parameter is 0.089. This value has been tested for normality if the value is above 0.05 then the results are acceptable. This means that it explains that the temperature and wind speed do not affect the noise level at Yogyakarta International Airport. The possibilities that can physically affect the noise level are the pressure and speed of sound.